2021
DOI: 10.1038/s41598-021-92292-y
|View full text |Cite
|
Sign up to set email alerts
|

High level of fatty liver index predicts new onset of diabetes mellitus during a 10-year period in healthy subjects

Abstract: Fatty liver index (FLI), a predictor of nonalcoholic fatty liver disease, has been reported to be associated with several metabolic disorders. This study aimed to evaluate the relationship between FLI and new onset of diabetes mellitus (DM). We investigated the association of FLI with new onset of DM during a 10-year period in subjects who received annual health examinations (n = 28,990). After exclusion of subjects with DM at baseline and those with missing data, a total of 12,290 subjects (male/female: 7925/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In the original report about MAFLD, the use of FLI was recommended for detection of hepatic steatosis as a reliable biomarker 4 . Furthermore, there have been several studies showing that FLI is associated with the development of hypertension 54 , diabetes mellitus 55 , chronic kidney disease 56 and heart failure 57 . Third, since the recruited participants were all Japanese, the results obtained in the present study might not be applicable to other races.…”
Section: Discussionmentioning
confidence: 99%
“…In the original report about MAFLD, the use of FLI was recommended for detection of hepatic steatosis as a reliable biomarker 4 . Furthermore, there have been several studies showing that FLI is associated with the development of hypertension 54 , diabetes mellitus 55 , chronic kidney disease 56 and heart failure 57 . Third, since the recruited participants were all Japanese, the results obtained in the present study might not be applicable to other races.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is a known metabolic disease that increases foeto-maternal morbidity and mortality 35. Several authors have developed mathematical models to predict NAFLD in the general population 20 31 32. After validation, some countries started to use the FLI as a screening tool 36 37.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…The FLI is a simple and easy tool that includes waist circumference (WC), body mass index (BMI), serum triglyceride level and serum gamma-glutamyl transferase (GGT) to predict FL. It has been validated in several countries, such as Iran, Japan and China, and the results have confirmed that FLI has the ability to separate the NAFLD group from the non-NAFLD group, with an area under the curve (AUC) of >0.8 20 31 32. However, the applicability of FLIs in pregnancy has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 97%
“…Uric acid levels were positively correlated with the METS-IR, and FLI showed a significant positive correlation with the METS-IR. In addition, previous study have shown that the METS-IR was positively correlated with IR [ 7 ], while those with an elevated METS-IR had a higher risk of developing hypertension [ 33 ] and hypertension in turn increases the risk of HUA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Bedogni et al developed the fatty liver index (FLI) for the early prediction of fatty liver disease in the general population [ 6 ]. In addition to the definite predictive role of the FLI on fatty liver disease, several studies have suggested that the FLI correlates to the development of metabolic syndrome and its components and even has an early warning effect [ 7 – 10 ] on cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%